ELABORATION DES AMORCES DU GENE RPSL EN VUE DE L’ETUDE DE LA RESISTANCE D’E.coli AUX ANTIBIOTIQUES - Farah, Nesrine; Belhachemi, Souhila (My University, 2024)
This work proposes an innovative approach to study antibiotic resistance in E. coli. E. coli resistance to antibiotics was investigated by focusing on the RPSL gene, which plays a crucial role in this process. In this study, we utilized bioinformatics tools to design specific and efficient primers for Polymerase Chain Reaction (PCR), a fundamental technique in molecular biology. Initially, resources such as the National Center for Biotechnology Information (NCBI) and the Primer-BLAST tool were employed to design a series of primer candidates targeting the RPSL gene. Subsequently, we selected the most promising primer pairs based on stringent criteria, including specificity, optimal length, and appropriate melting temperature. We successfully identified primer pairs for amplifying the RPSL gene, with primer pair 2 meeting international standards (melting temperature: 59°C, length: 20 nucleotides, specific product: 494 base pairs, no non-specific products).
Keywords: The RPSL gene; NCBI; Primer; BLAST; Primers; Amplification; Nucleotides